Comparative venom gland transcriptomics ofNaja kaouthia(monocled cobra) from Malaysia and Thailand: elucidating geographical venom variation and insights into sequence novelty - Tan, K.Y.; Tan, C.H.; Chanhome, L.; Tan, N.H. (PeerJ, 2017)
Background: The monocled cobra (Naja kaouthia) is a medically important venomous snake in Southeast Asia. Its venom has been shown to vary geographically in relation to venom composition and neurotoxic activity, indicating vast diversity of the toxin genes within the species. To investigate the polygenic trait of the venom and its locale-specific variation, we profiled and compared the venom gland transcriptomes of N. kaouthia from Malaysia (NK-M) and Thailand (NK-T) applying next-generation sequencing (NGS) technology. Methods: The transcriptomes were sequenced on the Illumina HiSeq platform, assembled and followed by transcript clustering and annotations for gene expression and function. Pairwise or multiple sequence alignments were conducted on the toxin genes expressed. Substitution rates were studied for the major toxins co-expressed in NK-M and NK-T. Results and discussion: The toxin transcripts showed high redundancy (41-82% of the total mRNA expression) and comprised 23 gene families expressed in NK-M and NK-T, respectively (22 gene families were co-expressed). Among the venom genes, three-finger toxins (3FTxs) predominated in the expression, with multiple sequences noted. Comparative analysis and selection study revealed that 3FTxs are genetically conserved between the geographical specimens whilst demonstrating distinct differential expression patterns, implying gene up-regulation for selected principal toxins, or alternatively, enhanced transcript degradation or lack of transcription of certain traits. One of the striking features that elucidates the intergeographical venom variation is the up-regulation of α-neurotoxins (constitutes ~80.0% of toxin's fragments per kilobase of exon model per million mapped reads (FPKM)), particularly the long-chain α-elapitoxin-Nk2a (48.3%) in NK-T but only 1.7% was noted in NK-M. Instead, short neurotoxin isoforms were up-regulated in NK-M (46.4%). Another distinct transcriptional pattern observed is the exclusively and abundantly expressed cytotoxin CTX-3 in NK-T. The findings suggested correlation with the geographical variation in proteome and toxicity of the venom, and support the call for optimising antivenom production and use in the region. Besides, the current study uncovered full and partial sequences of numerous toxin genes from N. kaouthia which have not been reported hitherto; these include N. kaouthia-specific L-amino acid oxidase (LAAO), snake venom serine protease (SVSP), cystatin, acetylcholinesterase (AChE), hyaluronidase (HYA), waprin, phospholipase B (PLB), aminopeptidase (AP), neprilysin, etc. Taken together, the findings further enrich the snake toxin database and provide deeper insights into the genetic diversity of cobra venom toxins.